Aboriginal Australians : first nations of an ancient continent - Muecke, Stephen, 1951-; Shoemaker, Adam. (London : Thames & Hudson, 2016)
In the 18th century, as European colonization proceeded apace, one continent remained to be discovered, the mythical Terra Australis incognita. This, the largest island-continent, had been inhabited for over 60,000 years by the Aborigines, who were described by the first explorers as the 'miserablest people in the world'. This perception was the beginning of a deep and long-lasting misapprehension, which the authors resoundingly dispel in this lively social and cultural history. They explore how the aborigines actually came to be in Australia, their extraordinary rituals and 'Dreamings', and the importance of 'kin' to their social structures. A chapter is devoted to the aborigines' often atrocious treatment at the hands of white settlers, and the pervasive racial prejudice that remained enshrined in the Australian constitution until 1967. The final section deals with the massive indigenous cultural renaissance over the past four decades, and discusses how Aboriginal art - be it Central Desert acrylic art, batik, contemporary urban painting, sculpture or traditional bark painting - has become a flagship for Australian culture.
Includes bibliographical references (p. 120-121) and index.
Keywords: Aboriginal Australians -- History; Aboriginal Australians -- Social life and customs